Historical aspects of the formation and development of the sector labor law - Вишновецька, С. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In this article is explored the features of historical development of the field of labour law whichis extraordinarily important and necessary for prognostication of ways and methods of subsequent development and perfection of modern labour right of Ukraine.